2009
DOI: 10.1161/atvbaha.108.181925
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Vascular Smooth Muscle NADPH Oxidase 1 (Nox1) Contribution to Injury-Induced Neointimal Formation

Abstract: Objective-Vascular NADPH oxidases (Noxes) have been implicated in cardiovascular diseases; however, the importance of individual Nox homologues remains unclear. Here, the role of the vascular smooth muscle cell (VSMC) Nox1 in neointima formation was studied using genetically modified animal models. Methods and Results-Wire injury-induced neointima formation in the femoral artery, along with proliferation and apoptosis, was reduced in Nox1 y/Ϫ mice, but there was little difference in Tg SMCnox1 mice compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
209
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(221 citation statements)
references
References 52 publications
10
209
0
1
Order By: Relevance
“…Using Nox1-deficient mice, Lee et al observed that proliferation and migration were reduced in cultured Nox1 y/-VSMCs. This finding indicates that Nox1 plays an important role in VSMC migration, proliferation, and extracellular matrix production [17].…”
Section: Discussionmentioning
confidence: 95%
“…Using Nox1-deficient mice, Lee et al observed that proliferation and migration were reduced in cultured Nox1 y/-VSMCs. This finding indicates that Nox1 plays an important role in VSMC migration, proliferation, and extracellular matrix production [17].…”
Section: Discussionmentioning
confidence: 95%
“…It is regulated by the redox chaperone protein disulfide isomerase in vascular smooth muscle cells 80 and has been implicated in vascular smooth muscle cell migration, proliferation and extracellular matrix production, effects mediated by cofilin. 81 Nox2 is the catalytic subunit of the respiratory burst oxidase in phagocytes, but is also expressed in vascular, cardiac, renal and neural cells. 82,83 Human Nox2 is a highly glycosylated protein that runs with an apparent molecular mass of B70 to 90 kDa on SDS-polyacrylamide gel electrophoresis.…”
Section: Vascular Generation Of Rosmentioning
confidence: 99%
“…Coincidentally, recent reports have implicated the Nox1 system in these responses (18,19), therefore suggesting a potential link between EBP50 and Nox1.…”
Section: Significancementioning
confidence: 91%